A technical feasibility study on the establishment of an on-campus pharmacy at the University of the Philippines Manila - Disu, Lincoln Sam C.; Reyes, Raquel E.; Uy Cana, Diane M.
Community pharmacy practice predominates in the Philippines; however, the practice has focused mainly on sales transaction and dispensing of medications. There is therefore a need for the establishment of a pharmacy that will both serve as a model of education and practice development, such as, an on-campus pharmacy. This study aimed to determine the technical feasibility of establishing an on-campus pharmacy at the University of the Philippines Manila College of Pharmacy (UPCP). A needs analysis survey was administered to purposively-sampled 385 passers-by long Taft Avenue, new Pedro Gil Street. Key informant interviews with hospital pharmacists, drugstore business experts, faculty members of the UPCP and engineers were also conducted. Survey results showed that over-the-counter (OTC) drugs are usually used for fever, cough and colds, body ache and as vitamin supplements while prescription medicines are commonly used for infection, fever, cough, colds and for hypertension management. Moreover, the passers-by are interested on services that include blood pressure and blood glucose measurements, medication counseling and medication therapy management, that are all affordable and accessible. Faculty members said that the on-campus pharmacy can be a training ground for both the students and preceptors and as an income-generating project; the hospital pharmacists considered that such a pharmacy can offer value-added services and focus on a different target market instead of the Philippine General Hospital (PGH) patients. Consultation and interviews with engineers and drugstore business experts determined the technical requirements: site, facility, pharmacy lay-out, product mix, equipment, utilities, waste management and regulatory requirements. In general, it can be concluded that the establishment of an on-campus pharmacy is technically feasible. However, a full feasibility study and business proposal should be done to say that the on-campus pharmacy is feasible and sustainable.
Keywords: Pharmacy